2023
DOI: 10.3389/fimmu.2023.1273570
|View full text |Cite
|
Sign up to set email alerts
|

The impact of aging and oxidative stress in metabolic and nervous system disorders: programmed cell death and molecular signal transduction crosstalk

Kenneth Maiese

Abstract: Life expectancy is increasing throughout the world and coincides with a rise in non-communicable diseases (NCDs), especially for metabolic disease that includes diabetes mellitus (DM) and neurodegenerative disorders. The debilitating effects of metabolic disorders influence the entire body and significantly affect the nervous system impacting greater than one billion people with disability in the peripheral nervous system as well as with cognitive loss, now the seventh leading cause of death worldwide. Metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 653 publications
0
4
0
Order By: Relevance
“…“ACD” is characterized by abundant autophagosomes and autophagolysosomes in the cytoplasm, extensive cytoplasmic degradation, but an intact nucleus, typically not reliant on Caspase family activity ( 137 , 138 ). The concept of autophagy-related cell death is debated, as autophagy-mediated apoptosis and a distinct cell death mechanism (independent of apoptosis and necrosis) are all referred to as “ACD” ( 139 ). Whether autophagy promotes or inhibits apoptosis depends on the cell type, stress nature, and stress duration ( 140 ).…”
Section: Crosstalk Between Autophagy and Apoptosismentioning
confidence: 99%
“…“ACD” is characterized by abundant autophagosomes and autophagolysosomes in the cytoplasm, extensive cytoplasmic degradation, but an intact nucleus, typically not reliant on Caspase family activity ( 137 , 138 ). The concept of autophagy-related cell death is debated, as autophagy-mediated apoptosis and a distinct cell death mechanism (independent of apoptosis and necrosis) are all referred to as “ACD” ( 139 ). Whether autophagy promotes or inhibits apoptosis depends on the cell type, stress nature, and stress duration ( 140 ).…”
Section: Crosstalk Between Autophagy and Apoptosismentioning
confidence: 99%
“…This may lead to a less efficient oxidative phosphorylation process, resulting in the production of more free radicals and reactive oxygen species (ROS) ( Reid et al, 2018 ). ROS are a hallmark of oxidative stress and they can damage intracellular proteins, lipids, and DNA, leading to impairment of cellular function and structure, which has been implicated in the development of a variety of diseases including aging, diabetes mellitus, vascular endothelial cell injury, neurodegenerative diseases, and the onset of cellular senescence, strategies to replenish depleted NAD + pools can offer significant improvements of pathologic states ( Klimova and Kristian, 2019 ; Maiese, 2023 ). A decrease in NAD + levels directly affects the metabolism of the body’s three major energy substances: sugar, fat, and protein, inducing MetS ( Covarrubias et al, 2021 ).…”
Section: Potential Mechanisms Linking Nnmt To Metsmentioning
confidence: 99%
“…Oxidative stress is widely recognized as a major contributor to inflammation and arthritis. An increase in chemical reactions within the body, damage to antioxidant defense systems, and an imbalance between oxidants and antioxidants can lead to a sharp rise in ROS, culminating in the accumulation of reactive oxygen molecules and defects in DNA, RNA, and proteins ( 124 ). Studies have demonstrated that RES effectively scavenges radicals such as hydroxyl and superoxide, thereby inhibiting lipid peroxidation and DNA damage induced by excessive ROS production ( 125 ).…”
Section: Resveratrol and Its Derivatives In The Research Progress Of ...mentioning
confidence: 99%